2019
DOI: 10.1071/rd18109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of follicle size on bovine oocyte lipid composition, follicular metabolic and stress markers, embryo development and blastocyst lipid content

Abstract: This study assessed the lipid composition of oocytes from different follicle sizes and compared the expression of lipid-related genes and follicular fluid (FF) molecules between groups. We also investigated the functional consequences of differences on embryo development and blastocyst lipid deposits. Oocytes and FF were recovered from different follicle sizes. Oocytes from small (≤5mm) and large (≥6mm) bovine follicles were used to produce Day 7 expanded blastocysts (Day7Ex) and blastocysts that only became e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…A studies provided by Annes et al compared the expression of lipid-related genes and follicular fluid molecules between different bovine follicle sizes. It was demonstrated that ELOVL6 showed lower transcript levels in larger follicle-derived (≥6 mm) oocytes compared with the ≤2 mm group [26]. Another study provided a comprehensive description of stage-specific lipidome signatures in early bovine embryo development, via assessment the mRNA abundance of lipid metabolism-related genes (including both ELOVL5 and ELOVL6).…”
Section: Discussionmentioning
confidence: 99%
“…A studies provided by Annes et al compared the expression of lipid-related genes and follicular fluid molecules between different bovine follicle sizes. It was demonstrated that ELOVL6 showed lower transcript levels in larger follicle-derived (≥6 mm) oocytes compared with the ≤2 mm group [26]. Another study provided a comprehensive description of stage-specific lipidome signatures in early bovine embryo development, via assessment the mRNA abundance of lipid metabolism-related genes (including both ELOVL5 and ELOVL6).…”
Section: Discussionmentioning
confidence: 99%
“…Any type of stress conditions that oocytes face can potentially disrupts embryo development. Differences in the morphology (Nagai et al, 2015;Nagano, 2019), lipid composition, transcriptome, and embryo development (Labrecque et al, 2016;Annes et al, 2018) had already been described in the oocytes recovery from different follicle sizes. The bovine oocytes used for IVPE are recovered from follicles with 2 to 8 mm of diameter, before follicle divergence.…”
Section: Oocyte Quality and The Follicular Environment Effectsmentioning
confidence: 95%
“…The bovine oocytes used for IVPE are recovered from follicles with 2 to 8 mm of diameter, before follicle divergence. Generally, oocytes recovered from large follicles (> 6mm) present a greater potential of reaching blastocysts compared to oocytes recovered from follicles of 2 to 6 mm (Rizos et al, 2002;Fair, 2003;Labrecque et al, 2016;Annes et al, 2018).…”
Section: Oocyte Quality and The Follicular Environment Effectsmentioning
confidence: 97%
See 2 more Smart Citations